Caracterização estrutural de uma lectina da esponja marinha Chondrilla caribensis - Sousa, Andressa Rocha de Oliveira (2021)
The organisms have a great chemical diversity, being able to produce countless diferente compounds. Among these compounds are lectins, proteins or glycoproteins that have specific and reversible binding to carbohydrates, however they do not alter their properties and are not necessarily involved in their metabolism. The study of lectins and their protein-carbohydrate interactions are important, since the pattern of glycosylation of cellular components is influenced by physiological changes, such as the occurrence of diseases. Structural studies are relevant to solve and understand the physiological role within the organism and to evaluate its biotechnological potential. Although structural studies of lectins have been promoted for a long time, few sponges lectins have their primary strucuture determined and only one of them has its three-dimensional structure resolved. The objective of this work was to structurally characterize the lectin present in the marine sponge Chondrilla caribensis and to evaluate its potential in diferent biological activities. The primary structure of CCL was determined by mass spectrometry. The amino acid sequence of the protein consists of 142 amino acids with a calculated molecular mass of 15.443 Da. Lectin has a galectin-like domain architecture, a family of β-galactoside-binding lectins, and it is very widespread in the animal kingdom. The signature sequence of highly conserved domain in galectins was identified in CCL with some modifications observed also in other sponge galectins. The three-dimensional structure was predicted and the carbohydrate binding site was analyzed using molecular docking, where CCL exhibits a typical galectin structure consisting of a β-sandwich with two antiparallel β-sheets. The amino acids that interact with the CCL ligands at the monosaccharide binding site are mostly the same conserved in this family of lectins. The molecular function, the biological process and the location of the predicted protein, show that CCL is a typical galectin and can perform several diferent functions, both intracelular and extracelular. CCL is a molecule with antitumor potential against prostate carcinoma cells and breast adenocarcinoma, with low cytotoxicity against healthy cells, in addition to showing leishmanicidal activity with very promising results.